Why Bother with Historical Criticism?: Lessons for Biblical Studies from the Philosophy of History - Holland, Drew (The Asbury journal, 2022)
This article seeks to integrate insights from the philosophy of history to support the continued use of the historical-critical method in biblical studies. Though the historical-critical method has been muchmaligned within biblical criticism over the past seventy years, this essay attempts to demonstrate the value of investigating ancient Israel's past as part of a full fledged biblical criticism.